Literary Depiction of the Second World War in The Eagle has Landed by Jack Higgins - Galler, Ondřej (Univerzita Pardubice, 2019)
This thesis focuses on the World War Two setting of the book The Eagle has Landed by Jack Higgins. The theoretical part describes the genres of Alternative and Secret histories and provides a short description of the author. The following chapter is dedicated to the raid on Gran Sasso by Otto Skorzeny and provides a summary of the Second World War up until the plot of the book takes place. The final, practical, part of the thesis examines individual aspects of the story and compares them to historical sources to verify their historical plausibility.
Literární vyobrazení druhé světové války v díle Orel Přistál od Jacka Higginse
Keywords: Eagle has Landed; Higgins, Jack; Churchill, Winston; Second World War; history; Orel Přistál; Higgins, Jack; Churchill, Winston; druhá světová válka; historie